Improving the specificity of R2' to the deoxyhaemoglobin content of brain tissue: Prospective correction of macroscopic magnetic field gradients - Blockley, N; Stone, A (Elsevier, 2016)
The reversible transverse relaxation rate, R2', is sensitive to the deoxyhaemoglobin content of brain tissue, enabling information about the oxygen extraction fraction to be obtained. However, R2' is also sensitive to macroscopic magnetic field gradients, particularly at air-tissue interfaces where a large susceptibility difference is present. It is important that this latter effect is minimised in order to produce meaningful estimates of blood oxygenation. Therefore, the aim of this study was to implement a technique to prospectively correct for the effect of susceptibility induced magnetic field gradients on R2' weighted data. This was achieved by combining the Gradient-Echo Slice Excitation Profile Imaging (GESEPI) technique with an Asymmetric Spin Echo (ASE) pulse sequence. The main advantages of this approach are (i) shorter acquisition times, since a separately acquired magnetic field map is not required and (ii) simpler analysis, since retrospective correction for the effects of magnetic field gradients in postprocessing is not required. In these experiments we show that with this newly developed technique it is possible to correct the majority of grey matter voxels for the expected distribution of through-slice magnetic field gradients to produce maps of R2' in a short scan duration.